Clinical profile, antibiotic susceptibility pattern of bacterial isolates and factors associated with complications in culture‐proven typhoid patients admitted to an urban hospital in Bangladesh - Khatun, Halima; Islam, Shoeb Bin; Naila, Nurun Nahar; Islam, Syed Aminul; Nahar, Baitun; Alam, Nur Haque; Ahmed, Tahmeed (Wiley Online Library, 2022)
This article was published in the Tropical Medicine and International Health [© 2018 John Wiley & Sons Ltd ] and the definite version is available at : https://doi.org/10.1111/tmi.13037 The Journal's website is at: https://onlinelibrary.wiley.com/doi/full/10.1111/tmi.13037